Analisis Risiko di Bengkel Fabrikasi Menggunakan Metode Hirarc di PT. XYZ - Muhammad Raykhan Sehatta; Akhmad Basuki Widodo Widodo (Departemen Teknik Kelautan Universitas Hasanuddin, 2025)
In the work process, there is a potential danger from the lowest to the highest, with this prevention and control efforts can be carried out. The potential risk of danger is not only in the work process, but also in the mismanagement or operation of work tools, and the use of PPE (Personal Protective Equipment). The implementation of Occupational Health and Safety (K3) is an important aspect that companies need to pay attention to in an effort to reduce various operational potentials in every production activity. Seeing the problem, this research was carried out to reduce the potential danger of fabrication workshops in cutting, welding and grinding work at PT. XYZ The purpose of this research is to identify hazards, risk assessment in accordance with ISO 45001:2018 and risk control using the HIRARC (Hazard Identification, Risk Assessment, Risk Control) method. The results of this study can be known the factors that are potential hazards found 14 main factors that have the potential to cause work accidents in 6 activities, namely material removal, cutting (CNC & oxy-fuel gas), welding, grinding and housekeeping. Based on the risk level assessment in accordance with the provisions of the ISO 45001:2018 standard with a risk matrix that measures the level of severity and likelihood, the average result is in the Medium Risk category with a score range of 4-10, while some activities are in the Low Risk category, although there is no risk categorized as High Risk, the fabrication workshop requires comprehensive risk control. Risk control measures include engineering control, administrative control, the use of PPE, as well as the regulation of work ergonomic techniques to have the right control approach to reduce the risk of accidents and diseases caused by work.